Alcohol Consumption: An Overview of International Trends - Monteiro, M.; Rehm, J.; Shield, K.; Stockwell, Tim (2016)
© 2017 Elsevier Inc. All rights reserved. Alcohol consumption is a large risk factor for the global burden of disease. Both average volume of consumption and the patterns of consumption are important alcohol consumption dimensions that need to be measured when estimating the impact of alcohol on a population. Based on World Health Organization (WHO) guidelines and on the WHO Global Information System on Alcohol and Health (GISAH), this article provides an overview of alcohol consumption and alcohol-related problems, the methodological issues surrounding estimates of consumption, patterns of drinking, and the harms related to alcohol, and the uses of the WHO GISAH.